Q-switched erbium-doped fiber laser with molybdenum disulfide (MoS2) nanoparticles on D-shaped fiber as saturable absorber - Ahmad, Harith; Soltani, Soroush; Thambiratnam, Kavintheran (World Scientific Publishing, 2019)
In this study, short Q-switching laser pulses are generated by drop-casting two-dimensional Molybdenum Disulfide (MoS2) nanoparticles as saturable absorbers (SA) on a side polished optical fiber in a C-band laser cavity. The proposed laser is capable of generating highly stable Q-switched laser pulses at the wavelength of 1559.42nm with a maximum repetition rate of 73.96kHz, and a minimum pulse width of 1.93μs. The relatively high signal-to-noise ratio of 58.7dB indicates a highly stable output. The proposed SA can be applied in a variety of fields due to its ease of manufacturing and cost-effectiveness as well as its robust and compact design. © 2019 World Scientific Publishing Company.